2004
DOI: 10.1177/0363546503258868
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Anterior Cruciate Ligament Reconstruction in Adolescents with Open Physes

Abstract: There was no evidence that intentionally delayed anterior cruciate ligament reconstruction increased the rate of additional knee injuries. Delayed reconstruction is a valid treatment option for adolescents with open physes at injury. Absolute activity restriction is key to decreasing the risk of additional knee injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 36 publications
1
76
2
3
Order By: Relevance
“…Because ACL injury in children tends to occur within 6-12 months of skeletal maturity [28] some authors advocate short term non-operative management with delayed, anatomic ACL reconstruction. Woods and O'Connor [28] employed a protocol to delay reconstruction that included rehabilitation, absolute avoidance of pivoting activities and full time brace wear while awake. Compared to a control group who received acute reconstructions, they reported no increase in intra-articular injuries despite a mean delay of 70 weeks until ACL reconstruction.…”
Section: Non-operative Treatmentmentioning
confidence: 99%
“…Because ACL injury in children tends to occur within 6-12 months of skeletal maturity [28] some authors advocate short term non-operative management with delayed, anatomic ACL reconstruction. Woods and O'Connor [28] employed a protocol to delay reconstruction that included rehabilitation, absolute avoidance of pivoting activities and full time brace wear while awake. Compared to a control group who received acute reconstructions, they reported no increase in intra-articular injuries despite a mean delay of 70 weeks until ACL reconstruction.…”
Section: Non-operative Treatmentmentioning
confidence: 99%
“…The variability in return to sport rates among non-operated ACL injured children is high [26,36]. Janarv et al [26] from Sweden reported that 88% of their non-operated children were performing activities at their desired activity level, McCarrol et al [36] described that 42% attempted to return to sport after conservative treatment (all failed), while no children in Woods & O'Connors [52] study continued at their pre-injury activity level, due to the restrictions in their treatment algorithm. There seems to be a difference in the return to sport rates after non-operative treatment between the Scandinavian countries and the USA, although the materials are small not directly comparable.…”
Section: Discussiomentioning
confidence: 99%
“…Making an accurate diagnosis can be difficult as there is a spectrum of injuries including tibial avulsions, partial ACL tears, and complete tears, and there can be multiple barriers to performing an accurate examination in this patient population. Also, there is some controversy over the appropriate treatment of these injuries in the pediatric and adolescent patient, mostly out of concern for the physis and potential growth disturbances [4,[7][8][9]. If surgery is chosen, there is debate over the appropriate technique as well as graft choice.…”
Section: Introductionmentioning
confidence: 99%